Bangladesh national culture and heritage : an introductory reader - Ahmed, A. F. Salahuddin; Chowdhury, Bazlul Mobin; Khan, A. Majeed; Chowdhury, Abdul Momin; Shahed, Syed Mohammad; Independent University, Bangladesh (Dhaka : University Press Limited, 2022)
Contributed articles on history and civilization of Bangladesh in 19th and 20th century.
Includes bibliographical references and index.
GenEd (RS)
Keywords: Bangladesh -- History -- 19th century; Bangladesh -- History -- 20th century; Bangladesh -- Civilization -- 20th century; Bangladesh -- Civilization -- 19th century